Regular exercise behaviour and intention and symptoms of anxiety and depression in coronary heart disease patients across Europe: Results from the EUROASPIRE III survey. (January 2017) - Prugger, Christof; Wellmann, Jürgen; Heidrich, Jan; De Bacquer, Dirk; De Smedt, Delphine; De Backer, Guy; Reiner, Željko; Empana, Jean-Philippe; Fras, Zlatko; Gaita, Dan; Jennings, Catriona; Kotseva, Kornelia; et al.
Background: Regular exercise lowers the risk of cardiovascular death in coronary heart disease (CHD) patients. We aimed to investigate regular exercise behaviour and intention in relation to symptoms of anxiety and depression in CHD patients across Europe. Design: This study was based on a multicentre cross-sectional survey. Methods: In the EUROpean Action on Secondary and Primary Prevention through Intervention to Reduce Events (EUROASPIRE) III survey, 8966 CHD patients <80 years of age from 22 European countries were interviewed on average 15 months after hospitalisation. Whether patients exercised or intended to exercise regularly was assessed using the Stages of Change questionnaire in 8330 patients. Symptoms of anxiety and depression were evaluated using the Hospital Anxiety and Depression Scale. Total physical activity was measured by the International Physical Activity Questionnaire in patients from a subset of 14 countries. Results: Overall, 50.3% of patients were not intending to exercise regularly, 15.9% were intending to exercise regularly, and 33.8% were exercising regularly. Patients with severe symptoms of depression less frequently exercised regularly than patients with symptoms in the normal range (20.2%, 95% confidence interval (CI) 14.8–26.8 vs 36.7%, 95% CI 29.8–44.2). Among patients not exercising regularly, patients with severe symptoms of depression were less likely to have an intention to exercise regularly (odds ratio 0.62, 95% CI 0.46–0.85). Symptoms of anxiety did not affect regular exercise intention. In sensitivity analysis, results were consistent when adjusting for total physical activity. Conclusions: Lower frequency of regular exercise and decreased likelihood of exercise intention were observed in CHD patients with severe depressive symptoms. Severe symptoms of depression may preclude CHD patients from performing regular exercise.